PENGARUH VARIASI TEKANAN KOMPAKSI PANAS TERHADAP DENSITAS DAN KEKERASAN AMC DIPERKUAT SiO2 - Asep, Muhammad; ., Sugiyarto; ., Somawardi; Rusdy, Achmad; Sukanto, Sukanto (Machine : Jurnal Teknik Mesin, 2023)
Research on aluminum metal matrix composites reinforced with ceramics using powder metallurgy methods has recently been increasingly in demand to be developed. The goals of this study determined the effect of differences in compaction pressure on the density and hardness properties of the resulting composite. The research method used of is following the stages of the powder metallurgy process, which includes material preparation, mixing and compaction. The mixing of the composite constituent powders was carried out using the mechanical alloying method using a horizontal ball mill for 4 hours. While the hot compaction method used is two-way compression compaction, using a hydraulic pump. The matrix material used is recycled aluminum powder, and the reinforcing material is powder from tin mine tailing silica sand. The hot compaction process was carried out at 500 0C and held for 15 minutes. Two-way compacting pressure variations used 4400 Psi, 4500 Psi and 4600 Psi. Density testing refers to Archimedes with the ASTM B962-15 standard. Meanwhile, the hardness test used the Rockwell hardness testing machine, referring to the ASTM E18-15 standard. The results of the density test and hardness test showed a tendency for the value to increase with increasing compaction pressure applied. The highest density was 2.147 g/cm3 for a sample with a compaction of 4,600 Psi, with the highest hardness value being 53,11 HRB. Based on micro-photographs, it shows that the interlocking mechanical bonds at lower compaction pressures tend to be weak, fractures at the grain boundaries are clearly visible and the pattern of damage tends to show brittle/brittle fractures.